Bypassing P-Glycoprotein Drug Efflux Mechanisms: Possible Applications in Pharmacoresistant Schizophrenia Therapy - Hoosain, Famida G. (Biomed Res Int, 2015)
The efficient noninvasive treatment of neurodegenerative disorders is often constrained by reduced permeation of therapeutic agents into the central nervous system (CNS). A vast majority of bioactive agents do not readily permeate into the brain tissue due to the existence of the blood-brain barrier (BBB) and the associated P-glycoprotein efflux transporter. The overexpression of the MDR1 P-glycoprotein has been related to the occurrence of multidrug resistance in CNS diseases. Various research outputs have focused on overcoming the P-glycoprotein drug efflux transporter, which mainly involve its inhibition or bypassing mechanisms. Studies into neurodegenerative disorders have shown that the P-glycoprotein efflux transporter plays a vital role in the progression of schizophrenia, with a noted increase in P-glycoprotein function among schizophrenic patients, thereby reducing therapeutic outcomes. In this review, we address the hypothesis that methods employed in overcoming P-glycoprotein in cancer and other disease states at the level of the BBB and intestine may be applied to schizophrenia drug delivery system design to improve clinical efficiency of drug therapies. In addition, the current review explores polymers and drug delivery systems capable of P-gp inhibition and modulation.